Lung ultrasound in Italian neonatal intensive care units: A national survey. Issue 9 (20th June 2022) - Corsini, Iuri; Parri, Niccolò; Ficial, Benjamim; Ciarcià, Martina; Migliaro, Fiorella; Capasso, Letizia; Savoia, Marilena; Gizzi, Camilla; Clemente, Maria; Raimondi, Francesco; Dani, Carlo
Abstract: Introduction: Lung ultrasound (LU) is a noninvasive, bedside imaging technique that is attracting growing interest in the evaluation of neonatal respiratory diseases. We conducted a nationwide survey of LU usage in Italian neonatal intensive care units (NICUs). Methods: A structured questionnaire was developed and sent online to 114 Italian NICUs from June to September 2021. Results: The response rate was 79%. In the past 4 years (range: 2–6), LU has been adopted in 82% of Italian NICUs. It is the first‐choice diagnostic test in 23% of the centers surveyed. The main LU diagnostic applications reported were: pneumothorax (95%), respiratory distress syndrome (89%), transient tachypnea of the newborn (89%), plural effusion (88%), atelectasis (66%), pneumonia (64%), bronchopulmonary dysplasia (43%), congenital pulmonary airway malformation (41%), and congenital diaphragmatic hernia (34%). Thirty percent of participating centers calculated LU score routinely, but only seven units used it to predict the need for surfactant replacement. Sixty‐six percent of respondents learned the LU technique via a self‐training process, while 34% of them visited an expert in the field for one‐to‐one tuition. Conclusions: LU has a widespread use in Italian NICUs. However, the use of LU is extremely heterogeneous among centers. There is an urgent need to ensure standardization of clinical practice guidelines and to design and implement a formalized and accredited training program.